Collaboration between Laboratory Teams and Nursing Staff to Improve Diagnostic and Therapeutic Efficiency in Hospitals - Ahood Marie Maeed Al Moshera; Aisha Saleh Mohammed Asiri; Afnan Mohammed Abdullah Al-Shmmari; Sabreen Hamood Mohammed Aldawsary; Hamda Abdulrhman Ayed Aldraan; Awatif Dhaifallah Awam Alhazmi; Sarah Fahd Mohammed Al-Thumairy; Bishri Dhaifallah Awam Alhazmi; Khalil Ali Hussien Almalki; Rami Sultan Hussein Asiri; Ahmed Essa Abdu Tawhari; Hussam Mohammed Ahmed Munshet (International Journal of Medical Toxicology and Legal Medicine, 2024)
Very critical in optimizing the diagnostic and therapeutic processes in a hospital are collaborations between laboratory teams and nursing staff. This encourages effective communication and information flow to ensure timely and accurate clinical decisions. Nurses are frontline caregivers who gather necessary information about the patients and perform care based on the findings of the laboratories, while laboratory professionals provide the precise diagnostic data that will lead to treatment. This cooperative interaction fosters patient outcomes and supports the multi-professional approach in health care. This partnership through high technology, evidence-based practice, and peer respect enables effective, advanced healthcare and focused patient care.